1998
DOI: 10.1073/pnas.95.17.10055
|View full text |Cite
|
Sign up to set email alerts
|

Widespread expression of an autoantigen-GAD65 transgene does not tolerize non-obese diabetic mice and can exacerbate disease

Abstract: Glutamic acid decarboxylase (GAD)65 is a pancreatic ␤ cell autoantigen implicated as a target of T cells that initiate and sustain insulin-dependent diabetes mellitus (IDDM) in humans and in non-obese diabetic (NOD) mice. In an attempt to establish immunological tolerance toward GAD65 in NOD mice, and thereby to test the importance of GAD in IDDM, we generated three lines transgenic for murine GAD65 driven by a major histocompatibility complex class I promoter. However, despite widespread transgene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 81 publications
(78 reference statements)
2
37
0
1
Order By: Relevance
“…For example, various treatments with GAD protein, peptide or DNA by various routes of administration were shown to inhibit disease, and antisense GAD, expressed only in pancreatic islets, protected mice from diabetes (9, 10, 21, 29 -31, 33). Nonetheless, the incidence of diabetes was unchanged in GAD knockout mice (57), and expressing GAD as a transgene was not protective (in some lines disease was actually accelerated) (58). Recently, von Boehmer and colleagues (59) clearly demonstrated normal diabetes incidence in GAD Tg mice, despite complete tolerance to GAD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, various treatments with GAD protein, peptide or DNA by various routes of administration were shown to inhibit disease, and antisense GAD, expressed only in pancreatic islets, protected mice from diabetes (9, 10, 21, 29 -31, 33). Nonetheless, the incidence of diabetes was unchanged in GAD knockout mice (57), and expressing GAD as a transgene was not protective (in some lines disease was actually accelerated) (58). Recently, von Boehmer and colleagues (59) clearly demonstrated normal diabetes incidence in GAD Tg mice, despite complete tolerance to GAD.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, some of these T cells are driven so early toward the Th1 phenotype that these proinflammatory responses cannot be prevented by neonatal immunotherapy. Indeed, even the widespread expression of a GAD transgene early in the development of NOD mice does not prevent the spontaneous development of GAD autoimmunity (52).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the observation that robust T cell responses to crude islet preparations are detectable at early time points where only weak responses are found against the known autoantigens (21, 22). Recently, experiments with NOD mice engineered to express GAD65 ubiquitously have shown that such mice are not protected from diabetes, nor do they develop evidence of widespread autoimmunity distinct from that observed in NOD (62). Likewise, GAD65-deficient mice bred onto the NOD background are not protected from autoimmune disease (63).…”
Section: Identity Of Early Autoantigens and Role Of Early Islet-infilmentioning
confidence: 99%